2019
DOI: 10.1371/journal.pone.0204388
|View full text |Cite
|
Sign up to set email alerts
|

Vascular effects on the BOLD response and the retinotopic mapping of hV4

Abstract: Despite general acceptance that the retinotopic organisation of human V4 (hV4) takes the form of a single, uninterrupted ventral hemifield, measured retinotopic maps of this visual area are often incomplete. Here, we test hypotheses that artefact from draining veins close to hV4 cause inverted BOLD responses that may serve to obscure a portion of the lower visual quarterfield—including the lower vertical meridian—in some hemispheres. We further test whether correcting such responses can restore the ‘missing’ r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Additionally, to determine if our findings were not merely due to other covariates, we included the normalized mean BOLD signal and intra-individual variability in pRF estimates as additional covariates. The former is an important proxy for the location of large veins ( Boyd Taylor et al, 2019 ; Kurzawski et al, 2022 ), which are known to affect pRF estimates ( Boyd Taylor et al, 2019 ; Winawer et al, 2010 ). The latter is a proxy for the reliability of individuals’ retinotopic maps, which could vary across visual areas.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, to determine if our findings were not merely due to other covariates, we included the normalized mean BOLD signal and intra-individual variability in pRF estimates as additional covariates. The former is an important proxy for the location of large veins ( Boyd Taylor et al, 2019 ; Kurzawski et al, 2022 ), which are known to affect pRF estimates ( Boyd Taylor et al, 2019 ; Winawer et al, 2010 ). The latter is a proxy for the reliability of individuals’ retinotopic maps, which could vary across visual areas.…”
Section: Discussionmentioning
confidence: 99%
“…Among potential sources of measurement error are the presence of large veins running adjacent to regions of interest. Accordingly, by using the normalized mean BOLD signal as a proxy for the location of large veins ( Boyd Taylor et al, 2019 ; Kurzawski et al, 2022 ), studies have shown that voxels near these veins show lower mean BOLD signal, a phenomenon known as the venous eclipse, which affects pRF estimates, for example, in area hV4 ( Boyd Taylor et al, 2019 ; Winawer et al, 2010 ). As such, deviations in the expected mean BOLD signal could result in deviations from the expected retinotopic organization.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations